Evaluation of Noxious Consequence of Bark Extract of Onosma echioides Linn Root: Hematology, Biochemistry, and Histopathological Findings. (2nd January 2020) - Shoaib, Ambreen; Siddiqui, Hefazat Hussain; Badruddeen,; Dixit, Rakesh Kumar
Abstract: Onosma echioides is a perennial herb widely used for the treatment of various ailments such as sciatica, gout, and rheumatism. This study focused on toxicological assessment of bark extract of O. echioides root. In subacute toxicity study, 20 Sprague Dawley rats (140 ± 10 g body weight) were randomly grouped into two groups of 10 rats each (5 male and 5 female). Effect of the n -hexane extract of O. echioides (100 mg/kg body weight/day) was studied for a period of 28 days using control and treated groups. Effects of the extract on body weight, food consumption, water intake, serum glucose, and hematology, biochemistry, and histopathology were evaluated. The histopathology was carried out to evaluate the degenerative changes in liver, heart, and kidney. Result of acute toxicity study showed dose-dependent increase in mortality. LD50 was found to be 1, 000 mg/kg body weight. The subacute toxicity data showed that the treated group did not show any change in behavior and urinalysis whereas an increase in body weight was observed in the male treated group. A significant but nontoxic effect was observed on food and water consumption. Significant increases in RBC (female treated group; ** p < .01), neutrophil (both male and female treated group; ** p < .01), MCV (female treated group, ** p < .01), MCH (both male and female treated groups; ** p < .01), and MCHC (both male and female treated groups; * p < .05) levels were observed; a significant changes were observed in total bilirubin (* p < .05), BUN (** p < .01), potassium (* p < .05), and ALT (** p < .01) levels. The relative organ weights of vital organs at this dose did not show any significant change. In conclusion, the toxicity data showed that the bark extract of O. echioides root does not possess any adverse effect at a fixed dose, which provides a support for its further safety study and biocompatibility application.